Simultaneous stochastic optimization of an open pit gold mining complex with supply and market uncertainty. Issue 4 (2nd October 2019) - Saliba, Ziad; Dimitrakopoulos, Roussos
ABSTRACT: A mining complex can include multiple mines, stockpiles, waste dumps and processing facilities. Traditional optimization approaches are often based on sequential optimization of the various components in the mining complex leading to suboptimal solutions. They also do not account for uncertainty in critical inputs, resulting in misleading forecasts. This paper presents an application of a stochastic framework that simultaneously optimizes mining, destination and processing decisions for a multi-pit, multi-processor gold mining complex. The framework accounts for supply and market uncertainty via stochastic orebody and commodity price simulations as inputs to a unified optimization model. The case study notably assesses the impacts of integrating market uncertainty as input that influences all components of the production schedule. Additionally, cut-off grade decisions are determined by the simultaneous optimization process, considering material variability and operating constraints while reducing the number of a-priori decisions to be made. This approach generates solutions that capitalize on the synergies between extraction sequencing, cut-off grade optimization, blending and processing while managing and quantifying risk in strategic plans, which ultimately leads to more metal production and higher net present values.